Biocompatible non-leachable antimicrobial polymers with a nonionic hyperbranched backbone and phenolic terminal units. Issue 39 (16th September 2022) - Arza, Carlos R.; Li, Xiaoya; İlk, Sedef; Liu, Yang; Demircan, Deniz; Zhang, Baozhong
Abstract : Nonionic hyperbranched polymers with phenolic terminal units were synthesized, which are non-leachable, non-cytotoxic, and show significant antibacterial effect. Abstract : This work aimed to develop biocompatible non-leachable antimicrobial polymers without ionic structures. A series of nonionic hyperbranched polymers (HBPs) with an isatin-based backbone and phenolic terminal units were synthesized and characterized. The molecular structures and thermal properties of the obtained HBPs were characterized by SEC, NMR, FTIR, TGA and DSC analyses. Disk diffusion assay revealed significant antibacterial activity of the obtained phenolic HBPs against nine different pathogenic bacteria. The presence of a methoxy or long alkyl group close to the phenolic unit enhanced the antibacterial effect against certain Gram positive and negative bacteria. The obtained nonionic HBPs were blended in polyester poly(hexamethylene terephthalate) films, which showed no noticeable leakage after being immersed in water for 5 days. Finally, these HBPs showed no cytotoxicity effect to MG-63 osteoblast-like human cells according to MTT analysis, and negligible hemolytic effect.